80th anniversary of the birthday of naval doctor, doctor of medical sciences, professor Yuriy Evlampievich Barachevskiy - A. V. Andreeva; R. I. Belyaeva; I. M. Kobelev; G. O. Samburov; G. B. Chetskaya (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
The article is dedicated to the 80th anniversary of the naval doctor, retired colonel of the medical service, full academician of the Academy of Military Sciences of the Russian Federation, doctor of medical sciences, professor Yuri Evlampievich Barachevsky, who taught at the naval department of the Arkhangelsk State Medical Institute (ASMI) for 40 years, and since 2009 has been the head of the department of mobilization training of healthcare and disaster medicine of the Northern State Medical University (NSMU). The authors of the article collected, summarized and analyzed data obtained from various historical sources: archival documents (personal files, orders of ASMI-NSMU), scientific literature; conducted interviews and supplemented the material with the memories of the hero of the day. Yuri Evlampievich Barachevsky is a talented doctor, healthcare organizer and teacher, who is warmly spoken of by colleagues, students and friends. He made a significant contribution to the development of mobilization training of healthcare and disaster medicine in the Arkhangelsk region, achieved great heights as a military doctor, as a teacher of a higher educational institution, as a scientist. The enthusiasm and determination of people like him are what makes medicine advance by leaps and bounds, which has a positive effect on the lives of millions of people. The career of Yuri Yevlampievich, presented in the article, is a bright page in the history of Russian medicine.